Societal values and their implications for contemporary graphic work (Journal of Namibian Studies : History Politics Culture, 2023)
Societal values are one of the aspects of relationships, individuals' behavior, and association with each other, as they are considered among the controls and standards of individual and social behavior. It is not possible to define societal goals and differentiate the nature of one community from another except through values. Given the industrial and technological development and the positive effects that emerged in terms of information technology, communication processes, and knowledge and cultural exchange within the local and global framework, these societal values appeared weakly or almost absent from their standards and origins, to appear at the same time societal values influenced by other cultures reflected in the cognitive and cultural production of other societal values. The researcher aims to study societal values and their reflections on the graphic achievement through the following question: (What is the effectiveness of societal values? And what are their reflections on the graphic achievement?). Therefore, the aim of the research contributed to identifying the reasons for the realization of societal values in the local graphic posters, and the theoretical framework included two chapters, the first (The concept of values, societal values in the design idea and its relationship to the graphic achievement) and the second (societal values and their employment through typographic elements) with indicators, and the third chapter includes research procedures and how to choose the research community and analyze sample forms. The research reached several conclusions, the most important of which are:1.Employing societal values in the design of the graphic poster enhances the areas of interdependence and cohesion and achieves the positive meaning of the concept of societal values that have nobility and originality.2.Employing graphic images related to the cultural aspect by promoting the components of values that reflect adherence to societal values and pride in their cultural and human component.